Stevens-Johnson syndrome/toxic epidermal necrolysis: treatment with low-dose corticosteroids, vitamin C and thiamine - Middendorf, Matthew Middendorf (BMJ Case Rep, 2019)
We present the case of a 33-year-old woman with no significant past medical history who was admitted to an outside hospital for the abrupt onset of fevers, malaise and a diffuse mucocutaneous rash. Her constellation of symptoms and presentation were most consistent with a diagnosis of Stevens-Johnson syndrome/toxic epidermal necrolysis overlap syndrome secondary to ibuprofen exposure. Her rash continued to worsen and she was transferred to our medical intensive care unit (ICU), where broad-spectrum antibiotics were discontinued and she was treated with supportive care as well as ‘low-dose’ intravenous hydrocortisone, ascorbic acid (vitamin C) and thiamine (HAT therapy). After starting this therapy, the patient demonstrated a dramatic response with rapid improvement of her cutaneous and mucosal lesions. She was tolerating a diet provided by the hospital on day 4 and was discharged from the ICU a few days later.